Using Audio Visual Media to Improve Listening Skills and Learning Motivation - Elma Pida; Imam Subari; Dian Permanasari (Master Program in Indonesian Language Education and The Institute for Research and Community Service STKIP PGRI Bandar Lampung, 2021)
This research aims to improve listening skills and learning motivation by using audio-visual media in seventh grade students of SMP Negeri 7 Mesuji. Classroom action research is a research in which the researcher collaborates with several parties, both principals, classroom teachers, and researchers simultaneously, with two cycles, each cycle having three meetings. The method used in this research is classroom action research (CAR). This study used the subject of class VII students of SMP Negeri 7 Mesuji. The population of this study amounted to 56 students. The entire population was sampled, so the sample was 56 students. Methods of data collection using checklist observations, interviews and documentation. Data were analyzed using qualitative and quantitative descriptive techniques. The results showed that the use of audio-visual media was effective in improving the ability to listen to fantasy stories for seventh grade students of SMP Negeri 7 Mesuji. This can be seen from the results of the study which showed that the students' listening ability during the pre-cycle only obtained an average score of 37.32 and this was included in the poor category. When the action was taken in the first cycle, the students' listening ability increased to 49.28 and was included in the sufficient category. Furthermore, in the second (second) cycle, the score reached 64.82 (Good). Likewise, in increasing learning motivation, the use of audio-visual methods also increases learning motivation. In the pre-cycle, the score of 48.35 was included in the sufficient category; in the first cycle the score is 54.78 which is included in the sufficient category, while in the second cycle the score is 68.21 which is included in the good category.